Aspects of Gut Microbiota and Immune System Interactions in Infectious Diseases, Immunopathology, and Cancer - Lazar, Veronica; Ditu, Lia-Mara; Pircalabioru, Gratiela Gradisteanu; Gheorghe, Irina; Curutiu, Carmen; Holban, Alina Maria; Picu, Ariana; Petcu, Laura; Chifiriuc, Mariana Carmen (Frontiers in Immunology, 2018)
The microbiota consists of a dynamic multispecies community of bacteria, fungi, archaea and protozoans, bringing to the host organism a dowry of cells and genes more numerous than its own. Among the different non-sterile cavities, the human gut harbors the most complex microbiota, with a strong impact on host homeostasis and immunostasis, being thus essential for maintaining the health condition. In this review we outline the roles of gut microbiota in immunity, starting with the background information supporting the further presentation of the implications of gut microbiota dysbiosis in host susceptibility to infections, hypersensitivity reactions, autoimmunity, chronic inflammation and cancer. The role of diet and antibiotics in the occurrence of dysbiosis and its pathological consequences, as well as the potential of probiotics to restore eubiosis is also discussed.